Depression Among Medical Students and Interns in a Selected Teaching Hospital in Southern Bangladesh - Rizwan, ASM; Akhter, Shahida (Journal of Medicine, 2026)
Background: Depression is one of the leading causes of human disability worldwide. Among vulnerable groups, medical professionals are disproportionately effect by depression.Almost 1 in 4 medical students, especially female, suffers from depression worldwide. Ironically, 80% of these cases are reported from low and middle income countries.This can impact not only the health of the sufferer but also all of those who receives medical care from them. Methods: This cross sectional study was conducted in Ad-din Sakina Women’s Medical College, Jasore. One hundred seventy seven participants including students of different batches and Intern doctors were enrolled by convenience sampling in this study. A self administered form including nine item Patient Health Questionnaire (PHQ-9) was used to collect data from September 2024 to April 2025. SPSS was used to run the statistical analayis. Results: Overall 85.3% of participants were found to be in depressive spectrum with 10.7% falling into the category of severe depression. The highest mean PHQ-9 was found among fourth year students (14.48±5.17) and in the 24-26 year-old age group (11.66±5.9).The response “Feeling tired or having little energy” was reported mostly (34.5%) amidst the nearly everyday category followed by Feeling bad about yourself – or that you are a failure or have let yourself or your family down” (31.1%). 11.3% despondence had suicidal ideation. Conclusion: The staggeringly high proportion of depressive symptoms should raise the alarm to take mental health of medical students and interns seriously. Every institute should have means to screen and diagnose depression and take actions accordingly to avoid the negative impacts of the condition including planned or completed suicide. J MEDICINE 2026; 27(1): 21-26